Charismatic phenomena in Europe in the 17th century: female political prophetism in France, Spain and Italy - Silvia Raucci (In Gremium. Studies in History, Culture and Politics, 2020)
The purpose of the present article is to analyse the evolution of the political and social perception that the mystical movements assumed during the Modern Age and in particular after the spiritual changes setted by the Council of Trent . There were analyzed three cases of charismatic women in the Europe of the Seventeeth Century (Margaret of Alacoque in France, Maria of Agreda in Spain, Giulia Di Marco in Italy ) closely linked to their own political context ,to underline the strong interdependence between the religious sphere and the civil sphere. The final goal of the work is to identify, in spite of the diversity of the stories and charisms of the three prophetesses,  a point of similarity: the same capillary method of use of  political power. The article wants to highlight a new concept of the role of the Saint in the Modern Era; not only a venerable or incorruptible figure, but a main character, aware of his social function and  conscious of the social utility of the mystical gift.